Long-term trends and future projections of the burden of diabetic nephropathy in China: a comprehensive analysis of GBD data from 1990 to 2036 - Zhang, Yan; Hou, Dong; Chai, Zihui; Li, Xizi; Shan, Chuchu; Zhao, Yuetong; Song, Siyuan; Tan, Ying; Yu, Jiangyi (Frontiers in Endocrinology, 2025)
BackgroundDiabetic nephropathy (DN) is a prevalent and serious microvascular complication of diabetes that poses a significant public health challenge and negatively impacts quality of life in China. The objective of this study was to evaluate the disease burden of type 2 diabetic nephropathy in China and to predict the trend of this burden over the next 15 years.MethodsThis study used the Global Burden of Disease (GBD) system to analyze trends in the disease burden of type 2 DN in China between 1990 and 2021. The study utilized prevalence, incidence, deaths, years of life lost (YLLs), years lived with disability (YLDs), and disability-adjusted life years (DALYs) for DN, along with their 95% uncertainty intervals (UIs). Secondly, joinpoint Regression, age-period-cohort, and decomposition analyses were employed to estimate the contribution of epidemiological changes to the DN burden. We used the inequality slope index (SII) and concentration index to assess absolute and relative cross-country inequalities in 1990 and 2021. Furthermore, Bayesian age-period-cohort (BAPC) models were employed to predict the future burden of DN from 2022 to 2036.ResultsFrom 1990 to 2021, the burden of DN in China continued to increase, reaching a total of 20,911,520 cases. The age-standardized prevalence rate (ASPR) was 1,053.92 per 100,000 people. The age-standardized incidence rate (ASIR) was 16.29 per 100,000 people, and the age-standardized death rate (ASDR) was 5.64 per 100,000 people. Age-standardized disability-adjusted life years (DALYs) were 122.15 per 100,000 people. In 2021, the overall burden of DN continued to increase, with the effect of age strengthening with increasing age. The incidence rate showed a sustained upward trend. Decomposition analysis revealed that population ageing was the main cause of the increased burden of DN in China. Predictive Analysis suggests that the ASIR will continue to rise from 2022 to 2036, while the ASDR will decrease.ConclusionDN in type 2 diabetes mellitus places a significant burden on China’s healthcare system, primarily due to an ageing population. The incidence rate is expected to increase over the next 15 years before declining. Given China’s large population and severe ageing, implementing a tiered prevention and control strategy, strengthening health education, and promoting early, effective prevention are imperative to alleviating the disease burden in China.